Telenursing: Implementation of Teleconsultations in a University Hospital (Research, Society and Development, 2024)
This article aims to report the implementation of nursing teleconsultations at the Hospital das Clínicas of the Federal University of Pernambuco. This is a retrospective experience report on the implementation of nursing teleconsultations in a University Hospital. The study was carried out at the Hospital das Clínicas of the Federal University of Pernambuco. Teleconsultations were carried out during the period from October 28, 2022 to July 31, 2023 with patients from the following outpatient specialties: Breastfeeding, Bronchoscopy, Pediatric Surgery, Colonoscopy, Colposcopy, Oncology Navigation, Orthopedics, Pediatrics, Pre-operative, Pet/CT and Kidney Transplant. All 16 nurses who carried out synchronous telecare, using the Telemedicine and Telehealth System, participated in the sample. The research was approved by the Research Ethics Committee, opinion number 6,686,606. Resulting in a total of 263 nursing teleconsultations, and it was found that the specialty with the highest rate of teleconsultations was Pediatric Surgery and Pediatrics (34.98%), with the lowest percentile in teleconsultations being Kidney Transplant (1.52%). Regarding the training of teleconsultants, this was (100%) with technical support for the patient and professional. It is concluded that the implementation of nursing teleconsultations in the hospital promoted a high level of patient care, with benefits for users, teleconsultants, and because it is a pioneering work among federal university hospitals, it could become a model for implementations in other hospitals.